CO2-brine flow-through on an Utsira Sand core sample: Experimental and modelling. Implications for the Sleipner storage field. (January 2018) - Falcon-Suarez, Ismael; Papageorgiou, Giorgos; Chadwick, Andy; North, Laurence; Best, Angus I.; Chapman, Mark
Highlights: Experimental assessment of CO2 injection in Utsira Sand formation sample. Pore fluid distribution and pressure inferred from resistivity and P-waves. New rock physics model combining patchy fluid distribution and squirt flow effects. Velocity-saturation relation of practical importance to CO2 plume monitoring. Empirical relations between pore pressure, seismic and geomechanical data. Abstract: Sleipner (North Sea) is the world's first commercial-scale carbon capture and storage (CCS) project, active since 1996, with ∼17 million tonnes of CO2 stored. The main reservoir, Utsira Sand, constitutes an ideal host formation of exceptionally high porosity-permeability and large lateral extent. However, the extensive seismic time-lapse, gravity and electromagnetic monitoring surveys deployed at Sleipner have not been well-supported by laboratory measurements. Here, we investigate the geophysical and geomechanical response of an Utsira core sample for the first time, using controlled inflation/depletion cycles at variable CO2 -to-brine fractional flow rates. Ultrasonic P-wave velocities and attenuations are measured together with electrical resistivity (converted into CO2 -saturation), along with continuous axial and radial strain monitoring. Ultrasonic velocity and attenuation data were simultaneously inverted and results extrapolated to field-scale seismic-frequencies using a new rock physics theory, which combines patchy fluid distribution and squirt flow effects. It provides a velocity-saturation relationship of practical importance to CO2 plume monitoring. Furthermore, by combining ultrasonic and deformation data, we report empirical relations between pore pressure changes and geomechanical effects in the reservoir, for different saturation ranges. Our dataset complements and constrains existing geophysical monitoring surveys at Sleipner and, more generally, improves the understanding of shallow weakly-cemented sand reservoirs.